2019
DOI: 10.3390/plants8020039
|View full text |Cite
|
Sign up to set email alerts
|

PbCOP1.1 Contributes to the Negative Regulation of Anthocyanin Biosynthesis in Pear

Abstract: The synthesis of anthocyanin in pear (Pyrus bretschneideri) fruit is regulated by light. However, little is known about the molecular mechanisms of pear fruit coloring mediated by upstream light-signaling regulators. Here, the photoresponse factors CONSTITUTIVE PHOTOMORPHOGENIC (COP) 1.1 and 1.2 were cloned from ‘Red Zaosu’ peel to study their functions in pear fruit coloring. The overexpression vectors pBI121-PbCOP1.1 and pBI121-PbCOP1.2 were constructed to analyze their effects on anthocyanin synthesis in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…It has been reported that PIF3 degrades rapidly after irradiation of dark-grown seedlings in a process controlled by phytochromes (Bauer et al, 2004). Transgenic pears overexpressing of PbCOP1.1 showed decreased expression levels of anthocyanin-related synthetic genes and negatively regulated the coloration of fruits (Wu et al, 2019). Through ubiquitination, COP1 degrades HY5, a promoter of anthocyanin biosynthesis, and thereby, reduces the accumulation of anthocyanin in apple (An et al, 2017).…”
Section: Sunlight Stimulates Coloration Of Apple Fruit By Down-regulating the Expression Of Light-responsive Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that PIF3 degrades rapidly after irradiation of dark-grown seedlings in a process controlled by phytochromes (Bauer et al, 2004). Transgenic pears overexpressing of PbCOP1.1 showed decreased expression levels of anthocyanin-related synthetic genes and negatively regulated the coloration of fruits (Wu et al, 2019). Through ubiquitination, COP1 degrades HY5, a promoter of anthocyanin biosynthesis, and thereby, reduces the accumulation of anthocyanin in apple (An et al, 2017).…”
Section: Sunlight Stimulates Coloration Of Apple Fruit By Down-regulating the Expression Of Light-responsive Genesmentioning
confidence: 99%
“…PIFs were found to interact with phytochromes and participate in anthocyanin biosynthesis by binding to the promoters of anthocyanin biosynthesis-related genes (Liu et al, 2015;Shin et al, 2007). The functional of COP1 on the expression of anthocyanin biosynthetic genes was recently studied in Arabidopsis (Maier et al, 2013), pear (Wu et al, 2019), and apple (An et al, 2017;Li et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The transient overexpression method referred to previous studies [16,17]. The complete coding sequences (CDS) of PbLAC4-like and PbMYB26 were ampli ed by PCR from 'Red Zaosu' cDNA and then fused into the multiple cloning site (MCS) of pGreen 0029-62SK vector respectively to form 62SK-PbLAC4-like and 62SK-PbMYB26 plasmids.…”
Section: Transient Overexpression Assay In Pear Fruitlet Peelmentioning
confidence: 99%
“…MYB10, MYB10b, ERF22, REVEILLE promoted the biosynthesis of anthocyanin by activating the expression of anthocyanin biosynthesis genes in pear [14][15][16]. COP1.1 and MYB120 were identi ed as inhibitory regulators of anthocyanin biosynthesis in pear [17,18]. bHLH3, MYB88, MYB124, NAC52 and in apple [19][20][21], MYB75, MYB90, MYB113 and MYB114 in Arabidopsis thaliana [22][23][24] also were shown to promote anthocyanin biosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Quercetin and kaempferol derivates accumulate in Arabidopsis seedlings ( Stracke et al, 2010b ) acting both as UV protectants and free-radical scavengers ( Agati and Tattini, 2010 ). UV-B mediated flavonoid accumulation is UVR8 dependent ( Demkura and Ballare, 2012 ; Morales et al, 2013 ), leading to an induction of CHS, chalcone flavanone isomerase (CHI), flavanone 3-hydroxylase (F3H) and flavonol synthase (FLS) ( Hideg et al, 2013 ), all of which are HY5 inducible ( Shin et al, 2013 ; Wu et al, 2019 ), Interestingly dihydroflavonol reductase (DFR) was only shown to be induced in UV-A conditions ( Morales et al, 2013 ). However, the role of UVR8 in the induction of DFR transcript is not COP1 regulated under UV-B conditions ( Oravecz et al, 2006 ) and therefore hints at an interaction between photoreceptors ( Morales et al, 2013 ) below 350 nm ( Morales et al, 2013 ; Rai et al, 2020 ).…”
Section: Uv Regulated Specialized Metabolites and Hormones Leading Tmentioning
confidence: 99%